(untitled) (International Journal of Engineering and Computer Science, 2015)
The purpose of this research is to build a machine learning model to predict the genre of a song. This paper analyzes a song as a wave and determines the factors involved and predicts the genre. Application of the model is primarily to automatize the process of genre identification which shall aid in building of music recommendation systems.